Specificity of running speed and agility in competitive junior tennis players - Leone, M.; Comtois, A. S.; Tremblay, F.; Leger, L. (Medicine and Science in Tennis, 2006)
The purpose of this research was to highlight the importance of the specificity of speed and agility on the performance of competitive junior tennis players. The participants (n=38) were assessed in two separate sessions using five different running speed and agility tests. The players (males, n=24; females, n=14) were evaluated for short sprints over four metres (two tests), 20 metres dash sprint (one test) and for sprints with changes of direction at various angles over 20 metres with and without hitting tennis balls (two tests). Test-retest correlations indicated that the five tests showed moderate to good reliability with values ranging from 0.704 to 0.830. Correlation coefficients among the five speed and agility tests showed low relationships (r=0.032 to 0.642). The results of this study suggest that speed and agility are very specific and must be assessed and developed in different tennis-related conditions. It has been shown that traditional linear sprint tests (20-40 metres) are not a good indicator of the player's running speed in real game situations. Indeed, assessment and training must be sport-specific for maximal efficiency.